The Cultural Aspects of Organizations and Their Influence on the Performance of Financial Management in the Regional Government of Jambi Province - Sudirman; Wasistiono, Sadu; Jeddawi, Murtir; Kawuryan, Megandaru W. (International Journal of Science and Society, 2024)
The Performance of Regional Financial Management (PKD) holds a crucial objective to ensure the achievement of sustainable development and community welfare through a commitment to the principles of good governance as mandated by Law Number 1 of 2022. The aim of this research is to analyze the extent of the influence of organizational culture on the performance of regional financial management in the Provincial Government of Jambi. A quantitative research method was employed, involving a sample of 445 respondents out of a population of 713 individuals. Data analysis utilized the Structural Equation Model (SEM) LISREL from the collected data through research questionnaires. The results of the study indicate that the path analysis measurement and t-value produce a significant influence of organizational culture on the performance of regional financial management. The dimensions of organizational culture that have the most significant influence are stability and attention to detail. The research findings yield a Standard Financial Performance Transformation Model as a novel discovery, where the performance of regional financial management is determined by the dimensions of stability and attention to detail.